Tinjauan Akuntansi Syariah Terhadap Profit Margin Pada Bisnis Multi Level Marketing (Studi Kasus Amway dan Oriflame) - Alvia Sugmania Putri; Isro’iyatul Mubarokah (Peneliti.net, 2023)
This study aims to thoroughly examine the importance of sharia accounting as a consideration in the MLM business regarding the profit margin that can be obtained, so that it is hoped that users or those with an interest in this MLM business will be more selective and can run it according to Islamic sharia. This research uses a descriptive method with a quantitative approach. Meanwhile, the research results come from the calculation of indicators between variables in the form of numbers that will be presented in writing. The results showed that the multi-level marketing system in the Amway and Oriflame companies is in accordance with Islamic sharia because it does not contain elements of fraud (gharar), reasonable prices for goods and clear career levels. And from the results of the 2018-2020 research on Amway and Oriflame, it shows that there is an influence on profit margins during that time span. However, both Amway and Oriflame both experienced a decrease in net profit margins.